An experimental technique to characterize interply void formation in unidirectional prepregs. (March 2017) - Helmus, Rhena; Kratz, James; Potter, Kevin; Hubert, Pascal; Hinterhölzl, Roland
Out-of-autoclave prepreg processing requires evacuation of volatiles in the early stages of processing to achieve an acceptable final void content. In this study, single prepreg plies were laid-up onto a glass tool to simulate a ply–ply interface, to gain an understanding of initial air entrapment and eventual removal mechanisms. The contact was recorded during processing with various edge breathing configurations to identify the relationship between evacuation pathways and contact evolution. The existence of preferential flow channels along the fibre direction of the material was demonstrated by characterizing the prepreg surface. Gas evacuation in those channels prevented contact during an extended ambient temperature vacuum hold. The contact between the prepreg and glass tool equilibrated around 80% during the ambient vacuum hold, and reached full contact at elevated temperature after a brief loss in contact due to moisture vaporization, when the resin pressure decreased to below the water vapour pressure.